Religiosity as Mediator in Reducing Misconduct of Adolescents-at-Risk - Sham, Fariza Md (Journal of religion and health, 2020)
In dealing with adolescents-at-risk who are involved in misconduct, the religious factor can be an effective approach. The objective of this research is to study the religious factor as a mediator in dealing with misconduct of adolescents-at-risk. This research is a survey study by design. The method used is quantitative through questionnaire using Likert scale. A study was done on 556 respondents comprising of adolescents within the range of ages 13 to 24 years. Factor analysis finds two main domains in misconduct of adolescents-at-risk, that is, family dysfunction and lack of religiosity. Mediation analysis is used to determine whether the religious factor may become the mediator for adolescent misconduct. Results of regression analysis show that the factor of family dysfunction contributes higher to the misconduct of adolescent-at-risk in comparison with the factor of religiosity. However, the issue of dysfunctional family itself is related with the lack of religiosity within family. A family which is concerned about religious education and practice will reduce the opportunity for adolescents to be involved in misconduct. Hence, to further empower the role of the religious factor in dealing with adolescents-at-risk, the family plays an important role in applying religious aspects in order for adolescents to be able to control themselves from any misconduct. Thus, results of mediation analysis show that 0.275 states the religious factor is a mediator for misconduct of adolescents-at-risk. This research will also focus on the relationship between lack of religiosity among adolescents, how it is related to dysfunctional family and how religiosity can be a mediator to reduce misconduct of adolescent-at-risk.